Differential modulation of NREM sleep regulation and EEG topography by chronic sleep restriction in mice - Kim, Bowon; Hwang, Eunjin; Strecker, Robert E.; Choi, Jee Hyun; Kim, Youngsoo (NATURE PUBLISHING GROUP, 2020)
Compensatory elevation in NREM sleep EEG delta power has been typically observed following prolonged wakefulness and widely used as a sleep homeostasis indicator. However, recent evidence in human and rodent chronic sleep restriction (CSR) studies suggests that NREM delta power is not progressively increased despite of accumulated sleep loss over days. In addition, there has been little progress in understanding how sleep EEG in different brain regions responds to CSR. Using novel high-density EEG electrode arrays in the mouse model of CSR where mice underwent 18-h sleep deprivation per day for 5 consecutive days, we performed an extensive analysis of topographical NREM sleep EEG responses to the CSR condition, including period-amplitude analysis of individual slow waves. As previously reported in our analysis of REM sleep responses, we found different patterns of changes: (i) progressive decrease in NREM sleep duration and consolidation, (ii) persistent enhancement in NREM delta power especially in the frontal and parietal regions, and (iii) progressive increases in individual slow wave slope and frontal fast oscillation power. These results suggest that multiple sleep-wake regulatory systems exist in a brain region-specific manner, which can be modulated independently, especially in the CSR condition.
Keywords: PERIOD-AMPLITUDE ANALYSIS; POWER SPECTRAL-ANALYSIS; CORTICAL SYNCHRONIZATION; SLOW WAVES; HOMEOSTASIS; DEPRIVATION; RAT; CONTINUITY; RESPONSES; DYNAMICS